Approaches to the "fuzzy front end" of innovation - Birgit Verworn; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 1999)
In new product development (NPD) unacceptably high failure rates have often been related to insufficiencies during the early development phases. Nevertheless, only little effort is devoted to the early phases, in theory as well as in practice, and managers often indicate the front end as being one of the greatest weaknesses in product innovation. Therefore, it is surprising that only little research has treated the so called fuzzy front end of innovation. In this paper we discuss if process models lead to success in the early development phases. Therefore, the discussion about process models for the whole innovation process is briefly summarized and findings applied to the fuzzy front end. Due to high uncertainties with a wide range between different innovations in the early phases, process models are found to lead to success for incremental innovations with low market and technological uncertainty only. For innovations with a high market and/or technological uncertainty, a learning-based approach is suggested.
urn:nbn:de:gbv:830-opus-1654
Keywords: 650; breakthrough innovation; fuzzy front end; innovation management; innovation process; new product development; stage-gate process